Development and in vitro evaluation of lyotropic liquid crystals for the controlled release of dexamethasone - Oyafuso, Márcia H. [UNESP]; Carvalho, Flávia C.; Takeshita, Tatiane M. [UNESP]; de Souza, Ana L. Ribeiro [UNESP]; Araújo, Daniele R.; Merino, Virginia; Gremião, Maria Palmira D. [UNESP]; Chorilli, Marlus [UNESP] (MDPI, 2017)
In this study, amphiphilic polymers were investigated as biomaterials that can control dexamethasone (DXM) release. Such materials present interfacial properties in the presence of water and an oily phase that can result in lyotropic liquid crystalline systems (LLCS). In addition, they can form colloidal nanostructures similar to those in living organisms, such as bilayers and hexagonal and cubic phases, which can be exploited to solubilize lipophilic drugs to sustain their release and enhance bioavailability. It was possible to obtain lamellar and hexagonal phases when combining polyoxyethylene (20) cetyl ether (CETETH-20) polymer with oleic acid (OA), N-methylpyrrolidone (P), isopropyl myristate (IM), and water. The phases were characterized by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS), rheological, textural, and bioadhesion analyses followed by an in vitro release assay. All samples showed elastic behavior in the rheology studies and hexagonal samples containing P and IM showed the highest adhesiveness. The drug release profile of all LLCS presented an average lag time of 3 h and was best fitted to the Korsmeyer-Peppas and Weibull models, with controlled release governed by a combination of diffusion and erosion mechanisms. These systems are potential carriers for DXM and can be explored in several routes of administration, providing potential advantages over conventional pharmaceutical forms.
Keywords: Amphiphilic polymers; Controlled release; Dexamethasone; Drug release; Kinetic model; Lyotropic liquid crystals; Nanostructured systems